TINJAUAN KRIMINOLOGI TERHADAP PENYALAHGUNAAN NARKOBA BAGI REMAJA DI WILAYAH KABUPATEN REMBANG - Siti Rosedevio T; Safik Faozi (Fakultas Hukum Universitas Stikubank, 2020)
Drug abuse by teenagers is a very serious problem. Because adolescents are candidates for the nation's next generation. Youth is a pillar of social strength which plays a very important role in the development of a nation and country. In the past decade, this problem has become rampant. Evidenced by the significant increase in the number of searchers or drug addicts, this makes me see the factors that cause drug crime by adolescents in Rembang Regency and the efforts made by the Rembang Resort Police in overcoming drug crimes by teenagers in Rembang Regency. This is interesting for the author to make a scientific paper on the criminological review of drugs for adolescents in the Rembang district. The method used by the author is sociological juridical, namely interviews and data interviews, both primary and secondary. According to the results of the study, the factors that most influence decisions are environmental factors and parental education. In daily life, there are still many adolescents who carry out abolition and the Rembang police in overcoming it have done several things, namely repressive efforts in the form of open coordination and repressive efforts in the form of closed coordination. Keywords: Abuse, Teenagers, Drugs